Taphonomic analysis of the Folsom bonebed at Lake Theo, Texas. (July 2015) - Buchanan, Briggs; Buchanan, Susan; Johnson, Eileen
The Lake Theo site is one of a handful of excavated Folsom-aged bonebeds on the Southern Plains. Despite the importance of this site, only limited research has been conducted on the collection. This limitation is a consequence of most of the bones being housed in sediment blocks removed from the field. This study makes use of recent efforts that have made the collection more accessible for research. Both taphonomic observations on the bone assemblage and statistical analyses that evaluate models of natural and cultural pre- and postdepositional processes now are reported. Taphonomic observations are consistent with the hypothesis that sediments buried the bonebed shortly after the carcasses were deposited. Forward stepwise multiple regression analyses indicate that the total products utility model is the best-fitting model. As such, the analyses suggest that Folsom hunters transported elements of higher utility away from the Lake Theo bison kill for further use. The actions of water flow and other natural destructive processes have not significantly influenced the observed skeletal element frequency.